La vulnerabilidad socioeconómica y el rezago escolar en el proyecto fortalecimiento al acceso, permanencia y titulación con énfasis en inclusión y a lo largo de la vida en la unidad educativa “Cumandá” del cantón Cumandá, provincia de Chimborazo periodo lectivo 2020-2021. - Muyulema Uzca, María Fernanda (2022)
Muyulema Uzca, M (2022). Subject: socio-economic vulnerability and school delay in the project for strengthening access, staying, and qualification with emphasis on inclusion and lifelong life in the educational unit "cumandá" of cantón cumandá, chimborazo province lecture period 2020-2021. (Grade thesis). Universidad Nacional de Chimborazo. Riobamba, Ecuador. The problem presented in the "Cumandá" Educational Unit is the high rate of early school dropout, which is why this study aimed to understand the relationship that exists between socio-economic vulnerability and school dropout in students of the "Cumandá" educational unit belonging to the FAT project. The theoretical foundation contemplates aspects, criteria on vulnerability, socio-economic and socio-economic vulnerability, and school backwardness methodologically. It had a mixed approach with a non-experimental nonexperimental design, field, and bibliographic research type, descriptive-explanatory type with scientific, deductive, and explanatory with scientific, deductive, analytical, inductive, and synthetic methods. The population was 300 observation units and four teachers. Its sampling was probabilistic, from which using a statistical formula, the sample was obtained, consisting of 88 students and four teachers. For data collection, two instruments were used: a structured interview guide for teachers and a questionnaire for students, consisting of ten questions posed to the students. Ten questions were posed according to the topic. The students were given a ten-question questionnaire, which is dichotomous and polynomial in nature. The results obtained were represented graphically with their due analysis and interpretation. This allowed to know relevant discoveries to the phenomenon investigated. The phenomenon was investigated. It was concluded that several factors cause school lag to increase significantly, which is why a seminar was developed as an alternative solution to prevent school lag at an early age.